2014
DOI: 10.1371/journal.pone.0109705
|View full text |Cite
|
Sign up to set email alerts
|

Computational Insights into the Inhibitory Mechanism of Human AKT1 by an Orally Active Inhibitor, MK-2206

Abstract: The AKT signaling pathway has been identified as an important target for cancer therapy. Among small-molecule inhibitors of AKT that have shown tremendous potential in inhibiting cancer, MK-2206 is a highly potent, selective and orally active allosteric inhibitor. Promising preclinical anticancer results have led to entry of MK-2206 into Phase I/II clinical trials. Despite such importance, the exact binding mechanism and the molecular interactions of MK-2206 with human AKT are not available. The current study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 39 publications
1
32
0
Order By: Relevance
“…Our data revealed that W80A conversion also renders both Akt1 and Akt2 insensitive to the MK-2206 inhibitor, a newer drug with enhanced affinity and improved target specificity [ 27 , 28 ]. Consistent with our data, recent molecular docking studies of Akt1 and MK-2206 identified W80 as a residue that mediates their interaction [ 43 ]. Importantly, whereas Akt1 W80A and Akt2 W80A mutants are both resistant to MK-2206, they are still dynamically regulated by insulin and their phosphorylation of downstream effectors is indistinguishable from that of their WT counterparts.…”
Section: Discussionsupporting
confidence: 91%
“…Our data revealed that W80A conversion also renders both Akt1 and Akt2 insensitive to the MK-2206 inhibitor, a newer drug with enhanced affinity and improved target specificity [ 27 , 28 ]. Consistent with our data, recent molecular docking studies of Akt1 and MK-2206 identified W80 as a residue that mediates their interaction [ 43 ]. Importantly, whereas Akt1 W80A and Akt2 W80A mutants are both resistant to MK-2206, they are still dynamically regulated by insulin and their phosphorylation of downstream effectors is indistinguishable from that of their WT counterparts.…”
Section: Discussionsupporting
confidence: 91%
“…MK2206 is an allosteric inhibitor of Akt, and it could bind to the Akt kinase domain, which is an allosteric site, resulting in a conformational change, and then block the ATP binding site. Moreover, MK2206 had been used as a selective allosteric inhibitor of Akt phosphorylation (27)(28)(29). We found that MK2206 signifi cantly blocked phosphorylation of Akt Ser473 and decreased the expression of the cyclin E and p27 ( P < 0.05) ( Fig.…”
Section: Ser2448mentioning
confidence: 74%
“…The AKT is a key player, whose activation and/or overexpression are commonly linked to resistance to chemotherapy or radiotherapy . The chemical compound inhibitors of AKT have huge potential for the treatment of various cancers …”
Section: Introductionmentioning
confidence: 99%